Pathogenesis of progressive scarring trachoma in Ethiopia and Tanzania and its implications for disease control: two cohort studies. - Matthew J Burton; Saul N Rajak; Victor H Hu; Athumani Ramadhani; Esmael Habtamu; Patrick Massae; Zerihun Tadesse; Kelly Callahan; Paul M Emerson; Peng T Khaw; David Jeffries; David C W Mabey; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Trachoma causes blindness through a conjunctival scarring process initiated by ocular Chlamydia trachomatis infection; however, the rates, drivers and pathophysiological determinants are poorly understood. We investigated progressive scarring and its relationship to conjunctival infection, inflammation and transcript levels of cytokines and fibrogenic factors. METHODOLOGY/PRINCIPAL FINDINGS:We recruited two cohorts, one each in Ethiopia and Tanzania, of individuals with established trachomatous conjunctival scarring. They were followed six-monthly for two years, with clinical examinations and conjunctival swab sample collection. Progressive scarring cases were identified by comparing baseline and two-year photographs, and compared to individuals without progression. Samples were tested for C. trachomatis by PCR and transcript levels of S100A7, IL1B, IL13, IL17A, CXCL5, CTGF, SPARCL1, CEACAM5, MMP7, MMP9 and CD83 were estimated by quantitative RT-PCR. Progressive scarring was found in 135/585 (23.1%) of Ethiopian participants and 173/577 (30.0%) of Tanzanian participants. There was a strong relationship between progressive scarring and increasing inflammatory episodes (Ethiopia: OR 5.93, 95%CI 3.31-10.6, p<0.0001. Tanzania: OR 5.76, 95%CI 2.60-12.7, p<0.0001). No episodes of C. trachomatis infection were detected in the Ethiopian cohort and only 5 episodes in the Tanzanian cohort. Clinical inflammation, but not scarring progression, was associated with increased expression of S100A7, IL1B, IL17A, CXCL5, CTGF, CEACAM5, MMP7, CD83 and reduced SPARCL1. CONCLUSIONS/SIGNIFICANCE:Scarring progressed in the absence of detectable C. trachomatis, which raises uncertainty about the primary drivers of late-stage trachoma. Chronic conjunctival inflammation appears to be central and is associated with enriched expression of pro-inflammatory factors and altered expression of extracellular matrix regulators. Host determinants of scarring progression appear more complex and subtle than the features of inflammation. Overall this indicates a potential role for anti-inflammatory interventions to interrupt progression and the need for trichiasis disease surveillance and surgery long after chlamydial infection has been controlled at community level.